2018
DOI: 10.1097/phm.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of a Multicomponent Training for Prospective Memory Among Healthy Older Adults

Abstract: This multicomponent prospective memory training improved prospective memory performance and activities of daily living and reduce negative mood (depression) and anxiety levels among healthy older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Five studies evaluated the overall impact of VRSs on BADLs [ 33 , 34 , 35 , 36 , 37 ] and three studies examined IADLs [ 38 , 39 , 40 ]. We also identified six studies which assessed the effectiveness of VRSs on the capacity to make transfers and twenty-one studies which reported on their effectiveness in improving functional ambulation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies evaluated the overall impact of VRSs on BADLs [ 33 , 34 , 35 , 36 , 37 ] and three studies examined IADLs [ 38 , 39 , 40 ]. We also identified six studies which assessed the effectiveness of VRSs on the capacity to make transfers and twenty-one studies which reported on their effectiveness in improving functional ambulation.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining fourteen studies did not design any intervention for the control group. Only five studies carried out a follow-up after the intervention [ 38 , 39 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations